Combating Corruption Legal Approaches to Supporting Good Governance and Integrity in Africa - Hatchard, John (Edward Elgar Publishing, 2014)
Drawing on numerous recent examples of good and bad practice from around the continent, this insightful volume explores the legal issues involved in developing and enhancing good governance and accountability within African states, as well as addressing the need for other states worldwide to demonstrate the 'transnational political will' to support these efforts
Keywords: Political corruption / Africa; Political corruption / Africa / Prevention; Political corruption; Political corruption / Prevention; Africa; Electronic books